2020
DOI: 10.1016/j.ijrobp.2020.01.043
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sequencing Radiation Therapy and Immune Checkpoint Inhibitors in the Treatment of Melanoma Brain Metastases

Abstract: Disclosure: J.O. reports editorial consultancy for American Cancer Society. M.K.K. reports a grant from Merck Pharmaceuticals, outside the submitted work. S.S. reports advisory role for Novocure. Authors responsible for statistical analysis: Statistical analysis of patient data was conducted by co-authors Manali Rupji and Jeanne Kowalski. Data availability: Sequence data generated in this study has been deposited in GEO Bank (accession number GSE131521). The source data underlying Figs. 1a, 1b, 2, 3b, and Supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 17 publications
(16 reference statements)
0
14
0
Order By: Relevance
“…This finding is in line with the recent metaanalyse of Petrelli et al showing that the addition of IT to RT is associated with improved OS (HR = 0.54, 95%CI 0.44–0.67; p < 0.001 ) compared to RT alone in patients treated with BM [ 24 ]. The interesting point is that RT given before or concurrently to IT seemed to provide better results than the reverse sequence [ 25 ]. Due to the small number of patients (19 received IT before RT, 17 after RT and 9 before and after), we were not able to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with the recent metaanalyse of Petrelli et al showing that the addition of IT to RT is associated with improved OS (HR = 0.54, 95%CI 0.44–0.67; p < 0.001 ) compared to RT alone in patients treated with BM [ 24 ]. The interesting point is that RT given before or concurrently to IT seemed to provide better results than the reverse sequence [ 25 ]. Due to the small number of patients (19 received IT before RT, 17 after RT and 9 before and after), we were not able to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Conceptually, using SRS prior to ICIs would put fewer activated T-cells at risk. In a retrospective analysis of melanoma BM, RT followed by ICI was compared to ICI followed by RT [77]. The RT followed by ICI group had superior survival as compared to the ICI followed by RT group.…”
Section: Timing and Sequencingmentioning
confidence: 99%
“…Irradiation in the form of EBRT is known to have several immunomodulatory effects; for instance, EBRT can enhance tumor immunogenicity by inducing immunogenic cell death and promoting the release of tumor-associated antigens while simultaneously reducing tumor immunogenicity by upregulating programmed death ligand 1 expression ( 85 ). Combining EBRT with immune checkpoint blockade antibodies targeting programmed death 1, programmed death ligand 1, and cytotoxic T-lymphocyte antigen 4 represents an attractive strategy to potentiate radiation-induced antitumor immunity and has produced encouraging results ( 86 , 87 ). Although little is currently known about the effects of TRT on tumor immunogenicity, preclinical studies have shown that TRT also leads to upregulation of programmed death ligand 1 expression and that combinations of TRT with immune checkpoint blockade can lead to improved survival ( 11 13 ).…”
Section: Radiosensitization Through Blocking Immune Checkpointsmentioning
confidence: 99%
“…Although little is currently known about the effects of TRT on tumor immunogenicity, preclinical studies have shown that TRT also leads to upregulation of programmed death ligand 1 expression and that combinations of TRT with immune checkpoint blockade can lead to improved survival ( 11 13 ). Several clinical trials combining TRT + programmed death 1 inhibitors are currently under way (e.g., NCT03325816 and NCT03658447), though it is likely that further optimization of when immunotherapy should be administered during TRT treatment will be required; as with EBRT, Chen et al noted in their preclinical studies that the benefits of combining TRT + anti-programmed death ligand 1 varies depending on whether the two treatments are given concurrently or sequentially ( 12 , 86 ).…”
Section: Radiosensitization Through Blocking Immune Checkpointsmentioning
confidence: 99%